Current perspectives and trend of nanomedicine in cancer: A review and bibliometric analysis - Pei, Zerong; Chen, Shuting; Ding, Liqin; Liu, Jingbo; Cui, Xinyi; Li, Fengyun; Qiu, Feng (Journal of controlled release, 2022)
The limitations of traditional cancer treatments are driving the creation and development of new nanomedicines. At present, with the rapid increase of research on nanomedicine in the field of cancer, there is a lack of intuitive analysis of the development trend, main authors and research hotspots of nanomedicine in the field of cancer, as well as detailed elaboration of possible research hotspots. In this review, data collected from the Web of Science Core Collection database between January 1st, 2000, and December 31st, 2021, were subjected to a bibliometric analysis. The co-authorship, co-citation, and co-occurrence of countries, institutions, authors, literature, and keywords in this subject were examined using VOSviewer, Citespace, and a well-known online bibliometrics platform. We collected 19,654 published papers, China produced the most publications (36.654%, 7204), followed by the United States (29.594%, 5777), and India (7.780%, 1529). An interesting fact is that, despite China having more publications than the United States, the United States still dominates this field, having the highest H-index and the most citations. Acs Nano, Nano Letters, and Biomaterials are the top three academic publications that publish articles on nanomedicine for cancer out of a total of 7580 academic journals. The most significant increases were shown for the keywords “cancer nanomedicine”, “tumor microenvironment”, “nanoparticles”, “prodrug”, “targeted nanomedicine”, “combination”, and “cancer immunotherapy” indicating the promising area of research. Meanwhile, the development prospects and challenges of nanomedicine in cancer are also discussed and provided some solutions to the major obstacles. [Display omitted] •Data of current nanomedicine in cancer were collected from the Web of Science.•Collected data were systematically analyzed through bibliometric analysis.•Many keywords of nanomedicine in cancer were intuitively analyzed.•Hotspots, emerging frontiers and trend of nanomedicine in cancer were investigated.•Development prospects and challenges of nanomedicine in cancer were discussed.